Sheep no more : the art of awareness and attack survival - Gillain, Jonathan T. (Post Hill Press, 2017)
"Weekly, there are major threats, mass killings, terrorist attacks, and even weather-related disasters--the list goes on. And this increasingly dangerous world includes more violent and deadly threats that are specifically targeting everyday civilians ... [Via this safety bible], ... you can make educated predictions using the new key questions of who, why, where, when, and how from the attacker's point of view"--Amazon.com.